(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The current state of organization of administrative activity agriculture does not meet the full requirements of the market economy that directly affects the efficiency of its operation. The peculiarity of the current stage of improving the management system is the lack of unity required new forms of production and management of their content. Improved management activities is one of the most pressing problems whose solution provides a stable position on the market and its economic development. In agriculture organization of administrative work carried out under the direct and indirect influence of various factors relating to the nature of socio-political system, ownership, industry-specific agricultural sector. Features agriculture as industry and determine the appropriate cycle management features and characteristics of practice management employees regarding their implementation, ie implementation of universal basic features of derivatives of general and specific (special) functions. Performance management functions in the business entity AIC achieved by using them in practice appropriate management practices of information management, analysis, setting goals, planning, organization, management and control.